The complete works - Fuller, Andrew 1754-1815 (De Gruyter, 2023)
Andrew Fuller (1754-1815) was a pastor whose ministry coincided with the revitalization of the English Calvinistic Baptist denomination of which he was a distinguished member. He was a pathbreaking theologian, apologist, and spiritual biographer, who throughout his career remained rooted in the local church. Yet despite his multiple achievements, Fuller was probably best known at the end of his life as a pioneering missionary statesman. He was one of the founders and principal advocates of the Baptist Missionary Society, serving as the new society's secretary from its inception in 1792 until his death. His Apology for the Late Christian Missions to India was published in 1808 to defend the BMS missionaries from those who wanted them recalled from 'British India' for damaging colonial interests. In the Apology, Fuller shares his passion for overseas cross-cultural mission, a passion which came to define his ministry for many of his contemporaries and also, to a significant degree, for subsequent generations. In the Apology Fuller advocates on their behalf. This new edition of the Apology includes a 30,000-word introduction setting the context, and full notes on the text itself. It is of interest to theologians and missiologists as well as specialists in the history of Christian cross-cultural mission, colonialism, and the intersection between the two